STUDY OF TRANSMISSION OF BRUCELLOSIS FROM CATTLES TO MAN - Al-ARKUAZI, Y. P . (The Iraqi Journal of Veterinary Medicine, 2000)
This study had been done on three veliges in Suara (Wasit). The study includes Bacteriological investeaation and specific tests for Brucella S.P. in cattle & man, so the results showed that there is a direct relationship between the infection in the human being and those of animals, depending on the positive serological results on human with and with out clinical symptoms. By estimation a significant titer of the antibodies type (IgG).in the cases of the acute infection the, (IgM)antibody is the predominate class, in addition to that the isolation and identification of Brucella abortus has been done from some cases of man & animals. It is important to mention that we found a significant titer of antibody (IgG) in infant baby with a breast feeding at the same time we found a same titer in his mother.